The Elamite world
1 online resource
Keywords: "Amongst the civilizations to participate in the dynamic processes of contact and interchange that gave rise to complex societies in the ancient Near East, Elam has remained one of the most obscure, at times languishing in the background of scholarly inquiry. In recent years, however, an increasing body of academic publications have suggested that the legacy of Elam was more considerable and long-lasting than previously estimated.The Elamite World assembles a group of forty international scholars to contribute their expertise to the production of a solid, lavishly illustrated, English language treatment of Elamite civilization, covering topics such as its physical setting, historical development, languages and people, material culture, art, science, religion and society. Also treated are the legacy of Elam in the Persian empire and its presence in the modern world. This comprehensive and ambitious survey seeks for Elam, hardly a household name, a noteworthy place in our shared cultural heritage. It will be both a valuable introductory text for a general audience and a definitive reference source for students and academics."--Provided by publisher.